Giant Primary Cutaneous Nodular Melanoma of the Forehead: A Case Report - Samantha Montandon; Charles Jefferson-Loveday; Matthew Sommerlad; Harnish P. Patel (Geriatrics)
Background: The incidence of melanoma is increasing globally. The estimated worldwide incidence is projected to increase from 324,635 cases in 2020 to 510,000 in 2040. In the UK, melanoma accounts for 4% of all new cases of cancer. Melanomas occurring in the skin of the head and neck represent 13% and 23% of cases in women and men, respectively. Prognostic indicators include presence of nodal or distant metastasis, ulceration, and Breslow thickness, where >4 mm thickness predicts poorest overall survival rates. Giant melanomas, a term generally applied to melanomas larger than 5–10 cm, are rare and often have a very poor prognosis. Clinical case: An 82-year-old female presented acutely with a 2–3-day history of delirium and urinary retention in February 2022. In addition, she was noted to have a large fungating growth on her forehead that obscured the bridge of the nose and had been slowly increasing in size for the past year prior to admission. She had initially presented in primary care with a small growth on her forehead but declined further investigations for fear of contracting COVID-19. She consented to having further assessment and management of the forehead mass. A shave biopsy revealed giant nodular melanoma, specifically, the largest melanoma of the face reported in the literature. Remarkably, our patient underwent a successful complete excision and skin grafting, with no evidence of recurrence or distal metastasis after 2 years of follow up. Conclusions: This case highlights the anxieties people felt about contracting COVID-19 when national guidelines recommended shielding that had resulted in further morbidity. Despite poor prognostic factors, clinically and histologically, our patient did not need any systemic anticancer therapy nor radiotherapy. She was well after 2 years follow up without any signs of recurrence.